Data-Driven Demand Forecasting Based on an Ensemble LSTM Model - Khalilpour, Kaveh; Chen, Xinying (Journal of Computer Science and Software Applications, 2026)
User participation in power grid dispatching can effectively enhance grid flexibility; however, the inherent uncertainty of user behavior constrains the development of demand response. To address this issue, an incentive-based demand response implementation framework is first established, and the mechanism by which load aggregators (LAs) integrate demand-side resources to participate in electricity market operations is analyzed. User behavioral responses under incentive policies are further transformed into demand elasticity.Subsequently, based on the long short-term memory (LSTM) network, a data-driven demand elasticity forecasting method using an ensemble LSTM model is proposed. To improve forecasting performance, the source data are processed through smoothing and scaling operations, and weighting coefficients are incorporated into the loss function to enhance model robustness. Case study results demonstrate that, compared with the conventional LSTM model and the k-nearest neighbor (kNN) forecasting method, the proposed approach reduces the average prediction error of user demand elasticity by 5.33% and 28.8%, respectively. For total load forecasting, the mean absolute percentage error (MAPE) is reduced by 2.06% and 3.09%, respectively. In addition, the effects of smoothing and scaling preprocessing techniques on forecasting accuracy are investigated based on the ensemble LSTM model. The results indicate that appropriate preprocessing of the original data can effectively improve prediction accuracy.